ARABISASI (TA‘RIB) DALAM BAHASA ARAB (Tinjauan Deskriptif-Historis) - Abdul Malik (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
As a responsive agent, language changes and adapts in accordance with the development of civilization. So does Arabic language. As the adaptation mechanism (ta‘rib), Arabic language has gone through some changes. New words emerge. Some words are formed from the language itself and some are from others. This study aims to focus on ta‘ri> b or Arabization of foreign words and its process. The periodic stages of this process are observed through the historical point of view while the phenomenon of the ongoing. Arabization is discussed through a descriptive analysis. The paper initially is discussing the loan words (dakhil) and formation words, along with the definition promoted by linguists about ta‘rib. Contemporary examples are exposed as a comparison.